2008
DOI: 10.1159/000156466
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence and Immunogenetics of Human Longevity

Abstract: At present, individuals can live up to 80–120 years, a time much longer than that of our ancestors, as a consequence of the improvements in life conditions and medical care. Thus, the human immune system has to cope with a lifelong and evolutionarily unpredicted exposure to a variety of antigens, which are at the basis of profound age-related changes globally indicated as immunosenescence, a multifaceted phenomenon that increases morbidity and mortality due to infections and age-related pathologies. The major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(112 citation statements)
references
References 342 publications
(204 reference statements)
5
106
0
1
Order By: Relevance
“…Our deficit for lung cancer is in contrast to the excess for the other populations. The similarities for lymphoid malignancies could reflect immunological perturbations (immunodepression in persons with HIV/AIDS and transplant recipients and immunesenescence/inflammaging (Ostan et al, 2008) in elderly persons with CKS), whereas the differences for solid cancers could reflect different lifestyles/risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our deficit for lung cancer is in contrast to the excess for the other populations. The similarities for lymphoid malignancies could reflect immunological perturbations (immunodepression in persons with HIV/AIDS and transplant recipients and immunesenescence/inflammaging (Ostan et al, 2008) in elderly persons with CKS), whereas the differences for solid cancers could reflect different lifestyles/risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic analyses have confirmed that the exhaustion of thymic output with advancing age was the basis of the deficient replacement of naïve T cells lost in the periphery (i.e., by death or conversion to memory/ effector cells) (Kohler et al 2005;Ostan et al 2008;Haines et al 2009;Weiskopf et al 2009). Whether this contributes to the inability of maintaining the T cell repertoire breadth in older adults, TREC values could not be immediately interpreted to reflect continuous thymic output of naïve T cells (Hazenberg et al 2003).…”
Section: Sj-trec: a Biomarker Of The Resting Naïve T Cell Pool Rathermentioning
confidence: 95%
“…This results from a shift from a CD4 + T helper cells, Th1-like cytokine response to a Th2-like response, and furthermore an increase in levels of proinflammatory cytokines (i.e., IL-6, tumor necrosis factor (TNF-α), as well as IL-1β, . While a wide range of factors has been claimed to contribute to this state (i.e., increased amount of adiposity, decreased production of sex steroid, and chronic health comorbid disorders) (Ostan et al 2008;Fulop et al 2010), this altered inflammatory response has also been attributed to the continuous exposure to CMVantigen stimulation and/or reactive oxygen species (Pawelec et al 2009;Brunner et al 2011;Larbi et al 2011). However, whether these parameters could provide a robust set of criteria for the determination of an individual's immunological status in the older old adults, further studies are still required in order to identify biomarkers that are identifiable earlier in life so that intervention strategies can be administered sooner rather than later (Govind et al 2012).…”
Section: Is T Cell-mediated Immunity Senescence a Quantifiable Disorder?mentioning
confidence: 99%
See 2 more Smart Citations